2022
DOI: 10.1186/s12879-022-07704-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced disinfection with hybrid hydrogen peroxide fogging in a critical care setting

Abstract: Background Environmental contamination contributes to hospital associated infections, particularly those caused by multi-drug resistant organisms (MDRO). This study investigated bioburden presence on surfaces in a critical care center’s patient rooms following typical environmental services (EVS) practices and following intervention with hybrid hydrogen peroxide™ (HHP™) fogging. Methods Upon patient discharge, following standard cleaning or cleanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The VHP approach is not mentioned. Khandelwal et al [31] investigated the effectiveness of a device utilizing a 7% HP solution for disinfection in intensive care wards. In comparison to manual cleaning, an aHP device reduced aerobic colony counts in the environment by 98% after a 42-minute operation.…”
Section: Improved Methods Of Cleaning and Disinfecting The Environmen...mentioning
confidence: 99%
“…The VHP approach is not mentioned. Khandelwal et al [31] investigated the effectiveness of a device utilizing a 7% HP solution for disinfection in intensive care wards. In comparison to manual cleaning, an aHP device reduced aerobic colony counts in the environment by 98% after a 42-minute operation.…”
Section: Improved Methods Of Cleaning and Disinfecting The Environmen...mentioning
confidence: 99%
“…HPV as a decontaminant provides an effective and practical method for reducing the environmental load of microorganisms resistant to several antibiotics, such as MRSA and VRE. Studies [ 66 , 67 ] have shown that HPV may significantly decrease the number of these bacteria on various hospital surfaces, thereby lowering the risk of healthcare-associated illnesses (HAIs). Khandelwal et al [ 66 ] conducted a study in a critical care setting and found that hybrid hydrogen peroxide fogging could lower the bacterial counts on crucial surfaces, implying that this strategy is more effective than regular cleaning practices and ultraviolet light use in removing MDROs.…”
Section: Application Of Hydrogen Peroxide Vapour Against Clinically R...mentioning
confidence: 99%
“…Studies [ 66 , 67 ] have shown that HPV may significantly decrease the number of these bacteria on various hospital surfaces, thereby lowering the risk of healthcare-associated illnesses (HAIs). Khandelwal et al [ 66 ] conducted a study in a critical care setting and found that hybrid hydrogen peroxide fogging could lower the bacterial counts on crucial surfaces, implying that this strategy is more effective than regular cleaning practices and ultraviolet light use in removing MDROs. Furthermore, a comprehensive review and meta-analysis by Marra et al [ 67 ] confirmed the efficacy of no-touch disinfection technologies like HPV, revealing a statistically significant reduction in infections caused by particular MDROs such as C. difficile and VRE.…”
Section: Application Of Hydrogen Peroxide Vapour Against Clinically R...mentioning
confidence: 99%
“…Disinfection with hybrid hydrogen peroxide (HHP) fogging in a critical care setting [9] Staphylococcus aureus, Pseudomonas aeruginosa with resistance to methicillin ATP bioluminescent sensing and microbial traditional method showed that HHP fogging provides up to 98% of bacterial removal from various surfaces in hospital rooms without use of UV light.…”
Section: The Application Of Bioluminescent Atp Sensing [Reference] Ma...mentioning
confidence: 99%
“…This method of analysis's application to detect the presence of various microorganisms is interesting and diverse, and it should be noted in the field of sanitary control of various objects. Here, ATP sensing is used to analyze various surfaces in hospitals and places intended for short-term stay of patients [4,5,9,10,14,15], surfaces of instruments used for examination and treatments of patients [7,8,11,12], and also as tools and places for slicing and cooking of food products [19,20], where sanitation is important for human health. The express analysis in real time and sensitivity of the bioluminescent determination of ATP, as well as the amount of total information obtained, make it possible to assess the degree of contamination by microbial cells from different points of examination, identify the main sites of cell pollutions and monitor the effectiveness of methods and reagents used for sanitary treatment.…”
Section: Main Modern Trends In the Use Of Bioluminescent Atp Determin...mentioning
confidence: 99%